Mechanism of endogenous hormones regulating gallic acid biosynthesis during the development of buds and leaves in tea plant (Camellia sinensis) - Shi, Yutao; Lu, Xiaofeng; Song, Qingying; Sun, Huan; Shen, Wujing; Huang, Ruiqi; Huang, Jiapeng; Wei, Yanfen; Xiang, Fumin; Wang, Xi; Tuo, Yanming; Lin, Jinke; et al. (Frontiers in Plant Science, 2025)
Gallic acid (GA), as a precursor of Epigallocatechin-3-gallate (EGCG) biosynthesis in tea plant, is one of the important components of tea flavor and has various health benefits. However, the mechanism of endogenous hormones regulating GA biosynthesis during the development of buds and leaves of tea shoots is still unclear. In this study, the buds and leaves of five different developmental stages of tea shoots were used as test materials to explore the mechanism of endogenous hormone signaling pathway regulating GA biosynthesis. The results showed that the decrease of D-erythrosyl-4-phosphate content and the increase of shikimic acid content affected the accumulation of GA content during the development of tea shoots. Jasmonic acid, abscisic acid, auxin, cytokinin, and gibberellin inhibited GA biosynthesis by down-regulating the expression of two CsaroDEs through twenty-three plant hormone signal transduction factors, such as CsMYC2, CsSNRK2, CsARR-A, and CsDELLA, respectively, which mediated the downregulation of sixteen transcription factors, such as CsMYB44, CsMYB108, and CsC2C2. CsMYC2 and CsSNRK2 co-mediated the downregulation of the expression of CsMYB44 and CsMYB108 in response to changes in endogenous JA and ABA content, respectively, and inhibited the expression of CsaroDE, thereby co-regulating GA biosynthesis. CsMYC2 may be a key interworking site for the endogenous Jasmonic acid and abscisic acid signaling pathways to jointly regulate GA biosynthesis. Our findings revealed the potential mechanism of endogenous hormones regulating GA biosynthesis during the development of buds and leaves of tea shoots and provided a scientific basis for the regulation of tea quality.